Deep Learning Approach Instructional Design Textbook in the Merdeka Curriculum to Enhance Pre-Service Teachers’ Teaching Readiness in Office Administration Education - Anis Susanti; Tusyanah; Hengky Pramusinto; Muhamad Nukha Murtadlo; Tri Murwaningsih (Economics Education Department Universitas Negeri Semarang, 2026)
This study aims to develop and examine the effectiveness of a Deep Learning Approach instructional design textbook in the Merdeka Curriculum to enhance pre service teachers’ teaching readiness in Office Administration Education. This research employed a Research and Development (R&D) method using the Borg and Gall model, including need analysis, planning, product development, validation, revision, and field testing. The experimental stage applied a quasi-experimental design with an experimental class using the developed textbook and a control class using conventional materials. The need analysis results indicate that students experience difficulties in understanding Learning Outcomes (LO), Learning Objectives (LOs), and the Sequence of Learning Objectives, as well as in designing assessment and instructional strategies aligned with the Merdeka Curriculum. The findings demonstrated that the textbook achieved a validity score of 78%, indicating acceptable quality for instructional use, while readability testing reached 85%, suggesting that the material was accessible and practical for students. The effectiveness test showed a statistically significant improvement after implementation (p < 0.05). Students in the experimental group demonstrated higher teaching readiness (85.16%, high category) than those in the control group (65.72%, moderate category). In addition, the N-Gain score of 61.79 indicated a moderate level of improvement in learning outcomes. These findings provide evidence that the developed textbook demonstrated validity, practicality, and effectiveness in supporting pre-service teachers’ teaching readiness within the context of the Merdeka Curriculum.